Self-Efficacy and Motivation as Predictors of Students’ Learning Outcomes Among Elementary Students - Camaddo, Airen (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of self-efficacy and motivation on the learning outcomes of Grade 5 and Grade 6 pupils in the Asuncion District, Division of Davao del Norte. Anchored on Bandura’s Social Cognitive Theory, Self-Efficacy Theory, Self-Determination Theory, and the Expectancy-Value Theory, the study determined the levels of self-efficacy, motivation, and learning outcomes; examined the relationships among these variables; and identified the domains that significantly predicted students’ academic performance. A quantitative descriptive-correlational research design was employed involving 300 Grade 5 and Grade 6 pupils selected through proportionate stratified random sampling. Data were collected using adopted and validated questionnaires measuring self-efficacy and motivation, while students’ learning outcomes were obtained from academic performance records. Mean, standard deviation, Pearson’s correlation, and multiple regression analysis were used to analyze the data. The findings revealed very high levels of self-efficacy, motivation, and learning outcomes. Significant positive relationships were found between self-efficacy and learning outcomes and between motivation and learning outcomes. Regression analysis showed that belief in personal ability significantly predicted students’ learning outcomes, whereas belief that ability grows with effort did not. Among the motivation domains, task value emerged as the only significant predictor of learning outcomes. The study concludes that students’ confidence in their abilities and the value they attach to learning tasks contribute substantially to improved academic performance. It recommends strengthening instructional practices and school programs that enhance students’ self-efficacy, emphasize the value of learning tasks, and promote meaningful learner engagement. The study supports Sustainable Development Goal 4 (Quality Education) by providing evidence that can help improve learner engagement and academic achievement. It also contributes to educational and socio-economic sustainability by informing instructional practices and school improvement initiatives that promote quality learning outcomes and lifelong learning opportunities.